KEBIJAKAN KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI MADRASAH SENDANGSARI PAJANGAN BANTUL - Muhamad Farizal (Universitas Islam Malang, 2021)
The policies made by a leader in educational institutions are the most important factors for the achievement of educational goals. This study aims to explore how madrasah principals improve the quality of education, specially in Madrasah Sendangsari Bantul. With the aim of the research are the aspects of (1) the policy of the head of madrasah in improving the quality of education in Madrasah Sendangsari, (2) the implementation of policies of the head of madrasah in improving the quality of education, (3) the implementation of policies of the head of madrasah in improving the quality of education at Madrasah Sendangsari Bantul. The research approach used is descriptive qualitative. Methods of data collection are carried out by means of observation, interviews and documentation. Based on the data obtained, the researcher found several findings that the head of madrasah has an important role in improving the quality of education at the institution led. As in the policy regarding the application of discipline to students and teachers, providing services to all students and all levels of institutions, establishing good communication to all levels of educational institutions, and implementing the nature of responsibility and tolerance.